Children’s Problems During the Preschool Transition: Views of Mexican Teachers - Urbina-Garcia, Angel; Kyriacou, Chris (European Scientific Journal, ESJ, 2018)
Transitioning from preschool to primary school, has been shown to be particularly challenging for children who must adapt to a new environment, set of rules, demands, behaviours and expectations. A number of studies in developed countries have shown that children consistently show problems during this transition, however research is scarce in developing countries. A sample of 30 Mexican teachers from preschool and first grade was recruited to examine common problems children face during this transition to primary school. Results revealed that teachers were somewhat to very concerned about this transition. Preschool teachers reported children showing behaviour problems and having difficulty following directions as the most common problems, while primary school teachers reported the same problems in addition to children showing difficulty taking turns. Teachers’ characteristics were associated to a number of children’s problems. Overall, Mexican children show similar problems to those reported in the international literature, however further studies are needed in Latin American contexts. Implications for policy and practice are discussed.